2016
DOI: 10.1007/jhep03(2016)188
|View full text |Cite
|
Sign up to set email alerts
|

3D supergravity from wrapped M5-branes

Abstract: Through consistent Kaluza-Klein reduction, we construct 3D N = 2 gauged supergravities corresponding to twisted compactifications of M5-branes on a product of constant curvature Riemann surfaces, including Kähler-Einstein four-manifolds. We extend the reduction to fermionic supersymmetry variations in order to determine the 3D Killing spinor equations and classify all timelike supersymmetric solutions. As a by-product, we identify an infinite class of new supersymmetric warped AdS 3 (Gödel) and warped dS 3 sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 110 publications
(272 reference statements)
3
17
0
Order By: Relevance
“…This fact was noticed in [45] for the model treated in section 6 (see related discussion in that section). Indeed, one sees that the BPS flow equations are generated by varying a single superpotential function, which in the present case is denoted by W 3 .…”
Section: Holographic Rg Flowsupporting
confidence: 54%
See 1 more Smart Citation
“…This fact was noticed in [45] for the model treated in section 6 (see related discussion in that section). Indeed, one sees that the BPS flow equations are generated by varying a single superpotential function, which in the present case is denoted by W 3 .…”
Section: Holographic Rg Flowsupporting
confidence: 54%
“…it is associated to a massless vector multiplet that does not mix with the 5d graviphoton, but 16 This model was discussed in [45]. In the same paper the uplift in 10d is constructed and the authors showed that the R-symmetry agrees with the canonical R-symmetry in 11D based on the existing classification, [17].…”
Section: M5 Branesmentioning
confidence: 98%
“…The results in that paper motivates a direct study of the R-charge extremization problem from the 1D perspective, following an analogous approach to the ones developed in [46][47][48][49] compactifying from AdS 5 to AdS 3 × S 2 .…”
Section: Conclusive Discussion: Open Problems and Further Investigationsmentioning
confidence: 61%
“…In many cases, the resulting solutions can be embedded in ten or eleven dimensions by using consistent truncation ansatze. Solutions of this type in the maximal N = 4 gauged supergravity with SO(5) gauge group in seven dimensions have been extensively studied in previous works [8,9,10,11,12,13,14,15], see also [16,17,18,19] for similar solutions in N = 2 gauged supergravity. For solutions in other dimensions, see [20,21,22,23,24,25,26,27,28,29,30,31,32,33] for an incomplete list.…”
Section: Introductionmentioning
confidence: 99%